Australasian College of Sports Physicians—position statement: the place of mesenchymal stem/stromal cell therapies in sport and exercise medicine. Issue 20 (23rd December 2015) - Osborne, Hamish; Anderson, Lynley; Burt, Peter; Young, Mark; Gerrard, David
Abstract : Purpose and scope: This Position Statement has been written expressly for members of the Australasian College of Sports Physicians (ACSP); however, it may also be of interest to the wider medical community, sporting organisations, athletes and the general community. It has been informed by a comprehensive review of the scientific literature and the opinions of kindred organisations. This statement outlines the use of mesenchymal stem cell (MSC) therapies in the broad context of Sport and Exercise Medicine, recognising that every medical practitioner should respect: (1) the evidence for the therapeutic use of MSCs and (2) the priority for patient health and welfare.